2010
DOI: 10.1002/pi.2802
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of 1,3‐dienes containing functional groups: 8. Free‐radical polymerization of 2‐triethoxysilyl‐ 1,3‐butadiene

Abstract: The presence of a bulky substituent at the 2‐position of 1,3‐butadiene derivatives is known to affect the polymerization behavior and microstructure of the resulting polymers. Free‐radical polymerization of 2‐triethoxysilyl‐1,3‐butadiene (1) was carried out under various conditions, and its polymerization behavior was compared with that of 2‐triethoxymethyl‐ and other silyl‐substituted butadienes. A sticky polymer of high 1,4‐structure ($E:Z \approx 8:2$) was obtained in moderate yield by 2,2′‐azobisisobutyron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Since butadiene derivatives bearing electronically withdrawing polar groups are difficult to be synthesized, and easily dimerized to form Diels–Alder adduct during polymerization process, the (co)­polymerization of polar butadiene derivatives has been far from successful . Hirao and Takenaka reported the anionic living polymerization of a series of silicon-containing butadiene derivatives and systematically investigated the influences of polymerization conditions on the microstructure of the resulting polymer . Stadler et al opened the door to access N , N -dialkyl-2-aminomethyl-1,3-butadiene polymers through anionic and radical polymerization techniques and further quaternized the tertiary amino groups to obtain ionic polymers .…”
Section: Introductionmentioning
confidence: 99%
“…Since butadiene derivatives bearing electronically withdrawing polar groups are difficult to be synthesized, and easily dimerized to form Diels–Alder adduct during polymerization process, the (co)­polymerization of polar butadiene derivatives has been far from successful . Hirao and Takenaka reported the anionic living polymerization of a series of silicon-containing butadiene derivatives and systematically investigated the influences of polymerization conditions on the microstructure of the resulting polymer . Stadler et al opened the door to access N , N -dialkyl-2-aminomethyl-1,3-butadiene polymers through anionic and radical polymerization techniques and further quaternized the tertiary amino groups to obtain ionic polymers .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the COE and CTA 2 loading up to 48 000 and 800 equiv, respectively, confirmed a high productivity of all ruthenium catalysts with effective turnover numbers (TONs) up to 48 000 (Table 2, entries 7-15). HG2 and G3 catalysts, the amount of CNF remained low (818wt%) (entries[16][17][18][19].…”
mentioning
confidence: 99%
“…Sato et al [147] reported a synthetic route of 2-(triisopropoxysilyl)-l,3-butadiene in 1984; since then, this kind of functional diene has attracted wide interest. In this route, 2-(triisopropoxysilyl)-1,3-butadiene is prepared using 1,4-dichloro-2-(trichlorosilyl)-2-butene and isopropyl alcohol as starting materials (Figure 14) [148,149]. Firstly, the solution of isopropyl alcohol in triethylamine is added dropwise to a THF solution of l,4-dichloro-2-(trichlorosilyl)-2-butene ( Figure 14a) at 0 • C. After stirring overnight at 20 • C, the mixture is heated to 60 • C and kept for several hours, followed by cooling to 0 • C. Hexane is applied to precipitate the inorganic salt, which is removed using Hyflo-Super-Cel" (Johns-Manville Co.).…”
Section: Polar-group Functionalized 13-butadienesmentioning
confidence: 99%